Credit risk in Islamic microfinance institutions: The role of women, groups, and rural borrowers - Toka S. Mohamed (17316967) (2023)
Using international data, we find that Islamic MFIs experience reduced credit risk by offering more groups loans, serving more women, and serving more borrowers in rural locations. Conventional MFIs benefit from fewer group loans, less loans to rural borrowers, and a greater focus on female borrowers. Our results contribute to microfinance and financial inclusion literature by highlighting the potential of tapping into the social dynamics within Muslim communities. We present encouraging insights for Islamic MFIs donors and managers on the possibility of promoting the financial inclusion of women and rural borrowers without compromising the quality of the credit portfolio. Other Information Published in: Emerging Markets Review License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ememar.2022.100994